Influence of an exercise program in low back pain in ambulance drivers - Pacheco, Débora (2022)
Occupational health aims to prevent occupational hazards, promote and protect the health of workers. Given the high prevalence of low back pain associated with work-related musculoskeletal injuries, it is important to study this topic. The functional incapacity in these individuals, drivers, comes from low back pain as a consequence of risk factors inherent to work activity. Exercise has been found to be beneficial when directed at lower back pain. To verify the effect of an exercise program on reducing the functional disability of low back pain in ambulance transport drivers.